2022
DOI: 10.1109/tps.2022.3189579
|View full text |Cite
|
Sign up to set email alerts
|

New Antenna Designs to Boost the Plasma Density in Helicon Sources

Abstract: Plasma can be generated using radio frequency (RF) electromagnetic waves for a large variety of applications, such as energy and propulsion generation. Often, the desire is to achieve higher densities for given input power and helicon sources have demonstrated a high efficiency. The design of the antenna that couples the wave plays a major role in the efficiency of generating the plasma particles. Many geometries were studied and compared, but the relationship between the antenna characteristics and the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Specifically, at a bias voltage of 1.7 V, the slope resistance of the dual S-PIN diodes is reduced by approximately 32.4% compared to the single S-PIN diode. This reduction in slope resistance also implies that the solid-state plasma region of the dual S-PIN diodes can achieve a higher carrier [9] Single S-PIN 100 0.9 [13] Single S-PIN 100 0.94 [15] Single S-PIN 30 0.7 This work…”
Section: Fabrication Of S-pin Diodes Based On Soimentioning
confidence: 89%
See 1 more Smart Citation
“…Specifically, at a bias voltage of 1.7 V, the slope resistance of the dual S-PIN diodes is reduced by approximately 32.4% compared to the single S-PIN diode. This reduction in slope resistance also implies that the solid-state plasma region of the dual S-PIN diodes can achieve a higher carrier [9] Single S-PIN 100 0.9 [13] Single S-PIN 100 0.94 [15] Single S-PIN 30 0.7 This work…”
Section: Fabrication Of S-pin Diodes Based On Soimentioning
confidence: 89%
“…The foundational concept of a reconfigurable solid-state plasma antenna was originally proposed by Fathy et al [6] in 2003. This concept offers a significant level of operational flexibility and enhanced integration compared to a gas-state plasma antenna [7][8][9][10][11][12][13][14][15]. Subsequent advancements in this field have been characterized by notable contributions.…”
Section: Introductionmentioning
confidence: 99%
“…The blue core appears and extends from upstream of the discharge tube to downstream as the power is increased. The presence of blue core is often used to represent the helicon plasma discharge entering W mode [11,26,[32][33][34]. Boswell [8] suggested that the blue core mode discharge was a sign that the helicon plasma discharge mode had jumped to wave mode.…”
Section: Axial Distributionmentioning
confidence: 99%
“…This leads to the idea that electrons are accelerated to ionization energy due to their capture by the larger field at the antenna. Chang et al [26] simulated the helicon plasma discharge coupled by a semi-helical antenna (m 1) under a uniform magnetic field to calculate the wave propagation and power deposition in the blue core. Ali et al [27] designed a modified quadrifilar helical antenna and determined the relationship between plasma characteristics and antenna topography.…”
mentioning
confidence: 99%